1999
DOI: 10.1093/gerona/54.2.m55
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Fever and Leukocytosis in Acute Surgical Abdomens in Octogenarians and Beyond

Abstract: Acute surgical abdomen in patients 80 years or older has a unique distribution of diagnoses. Although an increase in temperature and marked leukocytosis are not diagnostic of any particular illness, their presence should suggest certain specific surgical illnesses to the practicing clinician. Frequently, elderly patients with acute surgical abdomens present with a normal temperature and leukocyte count.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 18 publications
1
26
1
2
Order By: Relevance
“…Moreover, even in case of accurate pre-CT diagnosis, systematic unenhanced CT increased the diagnostic confidence level, as shown on the radar chart, with data points converging towards a single and accurate diagnosis with 100 % confidence. Secondly, as older patients with abdominal pain have a twofold higher surgery rate [1,4] and sixfold to eightfold higher mortality rates compared with younger adults [6,35,36], there is a tendency to more readily hospitalize older patients, irrespective of the clinical suspicion. Indeed, in patients for whom CT was not requested, unenhanced CT led to valid discharge in 15.7 % of patients for whom hospitalization would otherwise have been recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even in case of accurate pre-CT diagnosis, systematic unenhanced CT increased the diagnostic confidence level, as shown on the radar chart, with data points converging towards a single and accurate diagnosis with 100 % confidence. Secondly, as older patients with abdominal pain have a twofold higher surgery rate [1,4] and sixfold to eightfold higher mortality rates compared with younger adults [6,35,36], there is a tendency to more readily hospitalize older patients, irrespective of the clinical suspicion. Indeed, in patients for whom CT was not requested, unenhanced CT led to valid discharge in 15.7 % of patients for whom hospitalization would otherwise have been recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In the old, bacteremia [16,17], endocarditis [18,19], pneumonia [20,21], and meningitis [22] may present with lower fever than in the young. In a recent study of acute surgical abdomens in octogenarians, a substantial percentage of patients with acute cholecystitis, perforation, and appendicitis presented with temperatures !37.5ЊC [23]. Finally, a current study of the occurrence of nosocomial febrile illness in patients residing in an acute geriatric-medicine unit found that the mean "febrile" rectal temperature was only 38.1ЊC.…”
mentioning
confidence: 82%
“…This approach is especially interesting with respect to older populations, for which clinical diagnosis is a challenge because physical examination findings are not reliable predictors of or excluding factors for serious disease [8]. Moreover, surgical diseases are more frequent in elderly than in younger population and have a specific distribution [18]. Surgical delay has also been pointed out as being a crucial morbidity and mortality factor in older age groups [19].…”
Section: Millet Et Almentioning
confidence: 99%